The Role of Information and Communication Technologies in Postconflict Reconstruction - Kelly, Tim; Souter, David (Washington, DC: World Bank, 2014)
In this summary report and a series of country case studies, infoDev is exploring the transformative role that Information and Communication Technologies (ICTs) can have in post-conflict nations during the process of reconstruction. The case studies look at countries at different stages of post-conflict reconstruction in Afghanistan, Liberia, Rwanda and Timor-Leste, and post-revolution in Tunisia.